Distinct Molecular Signatures of Aging in Healthy and HIV-Infected Individuals. (1st February 2022) - Rinaldi, Stefano; Pallikkuth, Suresh; De Armas, Lesley; Richardson, Brian; Pan, Li; Pahwa, Rajendra; Williams, Sion; Cameron, Mark; Pahwa, Savita
Abstract : Background: Virally suppressed chronic HIV-infected individuals on antiretroviral therapy experience similar immune impairments as HIV-uninfected elderly. However, they manifest symptoms of premature immune aging such as suboptimal responses to vaccination at a younger age. Mechanisms underlying premature immune aging are unclear. Setting: The study site was University of Miami Miller School of Medicine. Methods: In this study, we aimed to identify molecular signatures of aging in HIV-infected (HIV) individuals compared with age-matched healthy control (HC) participants. Transcriptomic profiles of peripheral blood mononuclear cells collected cross-sectionally from study participants were evaluated using RNA sequencing, and genes and pathways associated with age and HIV status were identified and compared between study groups. Generalized linear modeling was used to identify transcriptional signatures associated with age. Results: Despite that fewer differentially expressed genes between young (<40 yrs) and old (>59 yrs) were observed in the HIV group, metabolic and innate immune activation pathways were associated with increasing age in both HIV and HC. Age was also associated with pathways involved with T-cell immune activation in HC and with interferon signaling pathways in HIV. We observed signs of precocious immune aging at the transcriptional level in HIV and defined a transcriptional perturbation associated with innate immunity and glucose metabolism induced by aging in both HC and HIV. Conclusion: In this study, we identified distinct molecular signatures predictive of age in HIV versus HC, which suggest precocious immune aging in HIV. Overall, our results highlight the molecular pathways of immune aging in both HC and HIV that may be targeted for additional mechanistic insights or in a therapeutic setting. Abstract : Supplemental Digital Content is Available in the Text.